Salvage Therapy for Relapsed or Refractory Acute Myeloid Leukemia - Mangan, James K. (SAGE Publications, 2011)
There are a significant number of patients diagnosed with acute leukemia who either fail to achieve remission or who relapse thereafter. Challenges in treating this patient population include accurately assessing prognosis of disease and whether remission can be achieved; assessing the ability of patients to tolerate aggressive salvage therapies; choosing a salvage therapy that is most likely to succeed; and identifying suitable patients for hematopoietic stem cell transplantation. Despite the development of a variety of new investigational therapies, relapsed or refractory acute myeloid Leukemia remains a difficult clinical problem. Clinicians will need to consider all currently available approaches, including cytotoxic chemotherapy, targeted agents, and allogeneic stem cell transplantation, to optimize outcomes.